Nursing students and nurses' knowledge and attitudes regarding children's pain: A comparative cross-sectional study - Amponsah A.; Oduro E.; Bam V.; Kyei-Dompim J.; Ahoto C.; Axelin A. (Public Library of Science, 2022)
Introduction
Nurses encounter children who report of pain of diverse and unknown causes in their professional work. The current study therefore assessed and compared nursing students and nurses’ knowledge and attitudes pertaining to children’s pain in the Ghanaian context. The goal of this was to have a baseline information to guide the development and implementation of the content for a sustainable educational programme (short-course) for nursing students and nurses in Ghana.
Methods
Between October and December 2018, a cross-sectional study was carried out among 554 final year nursing students and 65 nurses in Ghana. The Pediatric Nurses Knowledge and Attitudes Survey Regarding Pain (PNKAS) was used to collect data from participants who were affiliated to four educational institutions and eight hospitals. Data were descriptively and inferentially analyzed using chi-square test of independence, independent samples t-test and one-way analysis of variance (ANOVA).
Results
Our findings revealed that nursing students and nurses generally had unsatisfactory knowledge and attitudes towards pain management in children. Nursing students however, had significantly higher scores than nurses in the total PNKAS score and in 10 out of the 13 identified item-areas. Greater scores were obtained by nursing students in areas which were related to pain physiology, pharmacokinetics, pharmacology of analgesics and pain perceptions (p < .05). All the participating nurses could not accurately determine: the onset of action of orally administered analgesics, equianalgesia of orally administered morphine, and the right dosage of prescribed morphine for a child who consistently reported of moderate to severe pain.
Conclusion
Final year nursing students and nurses have unsatisfactory knowledge and attitudes regarding children’s pain; which reiterates the need for urgent and effective educational efforts in this area. Regular in-service training should be offered to post-registration nurses to enhance their pediatric pain knowledge and attitudes for improved pain care in children.